Análise da atividade antifúngica in vitro de 2-bromo-N-fenilacetamida frente às espécies de Candida provenientes de um hospital universitário - Sousa, Romulo Pereira de Moura (2019)
Systemic candidiasis, also known as invasive candidiasis, is an opportunistic fungal infection caused by yeasts of the genus Candida. The invasive form is the most serious manifestation due to its spread to other organs, promoting prolonged hospitalization and high morbidity and mortality rates. The treatment for this severe infection still has a small therapeutic arsenal, which is summarized in three classes: triazolic agents, the echinocandins and the polyenes. Although the first-line drugs (triazolic agents and echinocandins) are effective, some Candida species are naturally resistant and others develop acquired resistance, the latter having been occurring increasingly and causing great concern due to the appearance of fungal multiresistance. Faced with this worrying picture, the search for new pharmacotherapeutic alternatives has been constant, and one of the sources of potentially active substances are the synthetic compounds. Based on the pharmacological potential of the synthetic substances, this study investigated the in vitro antifungal activity of the synthetic compound 2-bromo-N-phenylacetamide by determining the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (CFM) of Candida isolates from patients with invasive candidiasis assisted at the Lauro Wanderley University Hospital, João Pessoa-PB, in the year 2017. In addition, it identified the etiological agents and their sensitivity profiles through the Candifast® Kit, compared to the identification performed through laboratory methods, and finally assessed the association of the test substance with fluconazole. Thus, the present study revealed that 25 cases of invasive candidiasis were diagnosed, of which 56% were from patients in the intensive care unit of the hospital, and C. albicans was the most common etiological agent (52%), and that of the 15 clinical isolates chosen to follow up on this research, 47% were resistant to fluconazole, of which six (06) isolates of C. albicans and one (01) of the C. parapsilosis complex. In the antifungal activity assays, the test substance had CIM50 of 8 μg/mL for C. albicans and 16 μg/mL for C. parapsilosis complex, and CFM50 of 16 μg/mL and 32 μg/mL, respectively. The association between 2-bromo-N-phenylacetamide and fluconazole did not show synergism or antagonism, being characterized as indifferent. Therefore, the present study revealed that in the year 2017, the majority of cases of invasive candidiasis came from inpatients in the intensive care unit of the university hospital, with C. albicans as the most common etiological agent and fluconazole as the only Candifast® kit which showed resistance (47%). In addition, this was the first study with the synthetic substance 2-bromo-N-phenylacetamide, which showed a strong fungicidal activity against clinical isolates of C. albicans and C. parapsilosis complex, however, this substance was indifferent when associated with fluconazole.